2023
DOI: 10.1073/pnas.2217189120
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic roles of metal- and ligand-protonated species in hydrogen evolution with [Cp*Rh] complexes

Abstract: Protonation reactions involving organometallic complexes are ubiquitous in redox chemistry and often result in the generation of reactive metal hydrides. However, some organometallic species supported by η 5 -pentamethylcyclopentadienyl (Cp*) ligands have recently been shown to undergo ligand-centered protonation by direct proton transfer from acids or tautomerization of metal hydrides, resulting in the generation of complexes bearing the uncommon η 4 -pentamethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…However, these new species bear exclusively endo -η 4 -Cp*H, with the special ring proton oriented toward the rhodium­(I) center. These findings, along with very recent time-resolved spectroscopic studies that have identified the transient hydride supported by bpy, [Cp*Rh­(bpy)­H] + , and allowed for its kinetic characterization, strongly support that transient [Cp*Rh] hydride complexes are involved in this chemistry . These hydrides form by protonation of the reduced forms and undergo proton-hydride tautomerization that results in the transfer of the proton to the Cp* ring.…”
Section: Introductionmentioning
confidence: 56%
See 4 more Smart Citations
“…However, these new species bear exclusively endo -η 4 -Cp*H, with the special ring proton oriented toward the rhodium­(I) center. These findings, along with very recent time-resolved spectroscopic studies that have identified the transient hydride supported by bpy, [Cp*Rh­(bpy)­H] + , and allowed for its kinetic characterization, strongly support that transient [Cp*Rh] hydride complexes are involved in this chemistry . These hydrides form by protonation of the reduced forms and undergo proton-hydride tautomerization that results in the transfer of the proton to the Cp* ring.…”
Section: Introductionmentioning
confidence: 56%
“…Based on the most recent kinetic data, protonation of the Cp* ring via proton-hydride tautomerism may not contribute significantly to catalysis under conditions involving strong acid (Reaction 1a). 13 Previous work has demonstrated that with an attached bipyridyl (bpy) ligand, the catalyst readily forms dihydrogen gas. 4,8 Efforts to further optimize the catalytic activity of this complex have been stymied by an inability to isolate the reactive Rh(III)H intermediate supported by bpy.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations